Establishing the Ideal Conditions to Create an Airway Fire Using a Porcine Airway Model - Andrew M. Bysice; Tyler Oswald; Luis E. Mendoza Vasquez; Francisco Laxague; M. Elise Graham; Ruediger Noppens; Kevin Fung (OTO Open, 2023)
Abstract Objective Airway fires are a rare but devastating complication of airway surgery. Although protocols for managing airway fires have been discussed, the ideal conditions for igniting airway fires remain unclear. This study examined the oxygen level required to ignite a fire during a tracheostomy. Study Design Porcine Model. Setting Laboratory. Methods Porcine tracheas were intubated with a 7.5 air‐filled polyvinyl endotracheal tube. A tracheostomy was performed. Monopolar and bipolar cautery were used in independent experiments to assess the ignition capacity. Seven trials were performed for each fraction of inspired oxygen (FiO2): 1.0, 0.9, 0.7, 0.6, 0.5, 0.4, and 0.3. The primary outcome was ignition of a fire. The time was started once the cautery function was turned on. The time was stopped when a flame was produced. Thirty seconds was used as the cut‐off for “no fire.” Results The average time to ignition for monopolar cautery at FiO2 of 1.0, 0.9, 0.8, 0.7, and 0.6 was found to be 9.9, 6.6, 6.9, 9.6, and 8.4 s, respectively. FiO2 ≤ 0.5 did not produce a flame. No flame was created using the bipolar device. Dry tissue eschar shortened the time to ignition, whereas moisture in the tissue prolonged the time to ignition. However, these differences were not quantified. Conclusion Dry tissue eschar, monopolar cautery, and FiO2 ≥ 0.6 are more likely to result in airway fires.